ISOLATION AND IDENTIFICATION OF PHOSPHATE SOLUBILIZING BACTERIA FROM WASTE DUMPING GROUND IN MUMBAI - Tuscano, Sinal John; Gajbhiye, Nilima (International Journal of Research -GRANTHAALAYAH, 2024)
Phosphate solubilizing bacteria can solubilize insoluble phosphate complexes and convert them into available forms that can be used by plants for better growth. Phosphorus in chemical fertilizers gets fixed in the soil and becomes unavailable for plant growth. It is important to find an alternative inexpensive and sustainable technology that could provide sufficient Phosphorus nutrition to plants. An efficient Phosphate solubilizing bacteria was isolated based on its solubilization zone on Pikovskaya’s agar. The amount of Phosphate solubilized by the bacterial isolate was 490.0 ug/ml which was significantly higher as compared to control S. aureus which was 131.0 ug/ml. The release of soluble P significantly correlated with a drop in pH from 7.00 to 3.85 indicating the acid production mechanism of Phosphate solubilization. The isolated bacterial strain could also mineralize organic sources of phosphate. It also showed potential to solubilize phosphate under stress conditions such as heavy metals and salt. The Phosphate solubilizing bacteria was identified by MALDI-TOF sequencing and was shown to belong to the genus Serratia. Therefore, the isolated bacterial strain shows a good potential to be used as a biofertilizer and provide phosphate nutrition to the plants sustainably.